Evaluating the potential of Kalanchoe pinnata, Piper amalago amalago, and other botanicals as economical insecticidal synergists against Anopheles gambiae - Sheena Francis; William Irvine; Lucy Mackenzie-Impoinvil; Lucrecia Vizcaino; Rodolphe Poupardin; Audrey Lenhart; Mark J. I. Paine; Rupika Delgoda (Malaria Journal)
Abstract Background Synergists reduce insecticide metabolism in mosquitoes by competing with insecticides for the active sites of metabolic enzymes, such as cytochrome P450s (CYPs). This increases the availability of the insecticide at its specific target site. The combination of both insecticides and synergists increases the toxicity of the mixture. Given the demonstrated resistance to the classical insecticides in numerous Anopheles spp., the use of synergists is becoming increasingly pertinent. Tropical plants synthesize diverse phytochemicals, presenting a repository of potential synergists. Methods Extracts prepared from medicinal plants found in Jamaica were screened against recombinant Anopheles gambiae CYP6M2 and CYP6P3, and Anopheles funestus CYP6P9a, CYPs associated with anopheline resistance to pyrethroids and several other insecticide classes. The toxicity of these extracts alone or as synergists, was evaluated using bottle bioassays with the insecticide permethrin. RNA sequencing and in silico modelling were used to determine the mode of action of the extracts. Results Aqueous extracts of Piper amalago var. amalago inhibited CYP6P9a, CYP6M2, and CYP6P3 with IC50s of 2.61 ± 0.17, 4.3 ± 0.42, and 5.84 ± 0.42 μg/ml, respectively, while extracts of Kalanchoe pinnata, inhibited CYP6M2 with an IC50 of 3.52 ± 0.68 μg/ml. Ethanol extracts of P. amalago var. amalago and K. pinnata displayed dose-dependent insecticidal activity against An. gambiae, with LD50s of 368.42 and 282.37 ng/mosquito, respectively. Additionally, An. gambiae pretreated with K. pinnata (dose: 1.43 μg/mosquito) demonstrated increased susceptibility (83.19 ± 6.14%) to permethrin in a bottle bioassay at 30 min compared to the permethrin only treatment (0% mortality). RNA sequencing demonstrated gene modulation for CYP genes in anopheline mosquitoes exposed to 715 ng of ethanolic plant extract at 24 h. In silico modelling showed good binding affinity between CYPs and the plants’ secondary metabolites. Conclusion This study demonstrates that extracts from P. amalago var. amalago and K. pinnata, with inhibitory properties, IC50 < 6.95 μg/ml, against recombinant anopheline CYPs may be developed as natural synergists against anopheline mosquitoes. Novel synergists can help to overcome metabolic resistance to insecticides, which is increasingly reported in malaria vectors. Graphical Abstract